2014
DOI: 10.1371/journal.pone.0098308
|View full text |Cite
|
Sign up to set email alerts
|

Poor Nutrition Status and Associated Feeding Practices among HIV-Positive Children in a Food Secure Region in Tanzania: A Call for Tailored Nutrition Training

Abstract: Undernutrition among HIV-positive children can be ameliorated if they are given adequate foods in the right frequency and diversity. Food insecurity is known to undermine such efforts, but even in food rich areas, people have undernutrition. As yet no study has examined feeding practices and their associations with nutrition status among as HIV-positive children in regions with high food production. We therefore examined the magnitude of undernutrition and its association with feeding practices among HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 41 publications
(67 reference statements)
8
71
1
Order By: Relevance
“…Like in other studies conducted in similar settings among HIV-positive children [9,10], adults were more likely to succumb to undernutrition when they had poor feeding practices such as consuming foods with low dietary diversity. Moreover, only a small proportion consumed protein-rich foods, fruits, or vegetables in their routine meals, similar to other studies [18][19][20].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Like in other studies conducted in similar settings among HIV-positive children [9,10], adults were more likely to succumb to undernutrition when they had poor feeding practices such as consuming foods with low dietary diversity. Moreover, only a small proportion consumed protein-rich foods, fruits, or vegetables in their routine meals, similar to other studies [18][19][20].…”
Section: Discussionmentioning
confidence: 52%
“…Like in other contexts, undernutrition among pre-ART individuals was associated with low wealth index [10,24]. Previous models have established associations between poverty and undernutrition, especially among PLWHIV [8].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…One previous study estimating contributions of different factors to the burden of under-nutrition attributed 43 % of the reduction in the prevalence of underweight children between 1970 and 2005 in developing countries to increases in women's secondary education [14]. Previous studies have shown that women with secondary education are better informed about optimal child care practices [8], have better practices in terms of hygiene [27,28], feeding [18] and childcare during illness [18,21,22], have a greater ability to use the health system [29], are more empowered to make decisions [28] and are more likely to have financial resources to care for and feed children [18]. There has been a slight increase in the percentage of women who have completed secondary education in Rwanda, from 1.2 % in 2005 [30] to 2.8 % in 2010 [10], and we hypothesize that further gains in women's education may translate into improved child nutrition outcomes [7,31,32].…”
Section: Discussionmentioning
confidence: 99%